Hydrogen from intermittent renewable energy sources as gasification medium in integrated waste gasification combined cycle power plants: A performance comparison. (1st January 2016) - Perna, Alessandra; Minutillo, Mariagiovanna; Jannelli, Elio
Abstract: In this paper the integration of the energy production from programmable (biomass, waste) and not programmable (solar, wind) renewable sources is examined as an opportunity for increasing the share of electricity from renewable power plants, in order to overcome the major obstacles to their extensive penetration into the grid. The integration is performed by using hydrogen from intermittent renewable energy powered-electrolysis as gasification medium in conventional or advanced gasification systems for the waste treatment. The proposed integrated energy system consists of three main sections: i) the hydrogen production island; ii) the gasification island; iii) the power island. The assessment of the system performance has been conducted by considering two gasification technologies: hydro-gasification and hydro-plasma gasification. The performances comparison has been carried out in terms of syngas composition, energy consumptions and electric efficiency. Results have pointed out that the electric efficiencies of the integrated energy systems are in the range of 40% and 43%. Furthermore, it is found that by combining the storage of intermittent renewable energy sources with a waste gasification combined cycle power plant it is possible to achieve better performance with respect to the performance that can be obtained by storage and waste to energy systems operating separately. Highlights: Integrated power plants based on renewable hydrogen and waste gasification are studied. Hydrogasification and hydro-plasma gasification are proposed for the waste treatment. The syngas from gasification unit is used as fuel in a combined cycle power plant. Numerical models are developed to evaluate the power plants behavior and performance.